1984
DOI: 10.1128/aem.48.4.813-817.1984
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic effects of benomyl on polyploid brewing yeasts: isolation of auxotrophic mutants

Abstract: An enrichment procedure after ethyl methanesulfonate mutagenesis and exposure to the fungicide benomyl yielded mutants auxotrophic for several amino acids from two polyploid Saccharomyces spp. Benomyl treatment was found to have a marked morphological effect on polyploid Saccharomyces cerevisiae, causing cells to adopt a characteristic doublet cell morphology in which buds are nearly as large as the parent cells. Experiments in which nuclear division was monitored in benomyl-induced doublet cells by Giemsa nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Due to the presumed diploidy or polyploidy of industrial yeast strains (12,17,21,22), screening for recessive mutations by replica plating has not been routinely used as it has been for haploids. Instead, mutants of industrial yeast strains have been isolated by positive selection for drug or stress resistance phenotypes (8,9,11,20,27,32,37,40,41,54) or by enrichment procedures (13,33,42,43). Here we show that mutants carrying auxotrophic recessive mutations can be routinely isolated in industrial sake strains by replica plating at frequencies ranging from 5.3 ϫ 10 Ϫ4 to 2.0 ϫ 10 Ϫ3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presumed diploidy or polyploidy of industrial yeast strains (12,17,21,22), screening for recessive mutations by replica plating has not been routinely used as it has been for haploids. Instead, mutants of industrial yeast strains have been isolated by positive selection for drug or stress resistance phenotypes (8,9,11,20,27,32,37,40,41,54) or by enrichment procedures (13,33,42,43). Here we show that mutants carrying auxotrophic recessive mutations can be routinely isolated in industrial sake strains by replica plating at frequencies ranging from 5.3 ϫ 10 Ϫ4 to 2.0 ϫ 10 Ϫ3 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, auxotrophic mutants of industrial yeasts have not been isolated routinely, possibly because the yeasts are diploid or polyploid. Previous efforts to obtain auxotrophic mutants of industrial strains used positive selection, such as 5-fluoroorotic acid (5-FOA) (40) or ␣-aminoadipic acid (41) selection, or enrichment with nystatin (43) or benomyl (13). Thus far, the isolation of auxotrophic mutants of industrial yeasts has been thought to be difficult without the use of special selection procedures.…”
mentioning
confidence: 99%
“…This reagent is known to be a mitotic arrester because of its reaction. Two phenomena induced by the reagent are autopolyploidization and micronucleation in nuclear division, both of which have been reported in plants, animal cells and microbes [2, 31. There are few reports about changing the nuclear nature of yeasts, except for a report on binucleate yeasts [4]. However, we found that the binucleate cells of Sacchuromyces cerevisiue could be produced by colchicine treatment [5].…”
Section: Introductionmentioning
confidence: 58%
“…In order to analyse the effect this aneuploidy had on the strain, the CCNV of the strain was altered by treating the strain with the antifungal agent methyl l-(butylcarbamoyl)-2-benzimidazolecarbamate, also known as benomyl. This drug is a well-known aneuploidy-inducing agent that destabilizes microtubules during mitosis and meiosis, affecting among other processes chromosome segregation, and has been extensively used for the study of aneuploidies in yeast ( Bilinski et al, 1984 ; Taylor-Mayer et al, 1988 ). Parental strain N2 was treated with Benlate ® (50% concentration of benomyl), provided by Dupont (E.I.…”
Section: Methodsmentioning
confidence: 99%